Study on the theory of ecological offsetting based on physical parameters and policy suggestions for coastal wetlands (Journal of agricultural resources and environment, 2020)
基于物质量的滨海湿地生态补偿机制的研究，对于推动滨海湿地生态补偿实践、推进资源的可持续利用和生物多样性保护具有重要意义。本研究详细论述滨海湿地物质量补偿的理论体系，包括物质量补偿的定义、补偿原则及特点、主要补偿方式，以及补偿主体和客体等；并阐明了物质量补偿与生态修复之间的区别，对补偿参考系和补偿率等概念做了详细阐述。构建适用于我国产权机制的物质量补偿运行模式，将受损滨海湿地列入主要补偿客体，并为我国滨海湿地生态补偿提出对策建议：实行物质量补偿与价值量补偿相结合的多层次补偿模式；构建补偿率核算方法，开展物质量补偿评估试点；加强市场化交易模式，建立多元化补偿运行方式；完善滨海湿地生态补偿的立法和管理工作，保障政策有效性；增加滨海湿地生态补偿投入资金，加强滨海湿地科普教育等。 The study of the offsetting mechanism for coastal wetlands based on physical parameters is of significance because it would promote the practice of ecological offsetting in coastal wetlands, the sustainable utilization of resources, and biodiversity conservation. The theoretical framework and system of ecological offsetting based on physical parameters was discussed, including the definition, principle and characteristics, main offsetting methods, and offsetting subjects and objects, and the difference between ecological offsetting and ecological restoration was clarified. Concepts such as offset baseline and offset ratio were described in detail. We propose that an ecologica